(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2020)
The article talks about the dramaturgical construction of the female characters of the show O Quadro de Todos Juntos by the puppetry group Pigmalião Escultura que Mexe and problematizes the representation of the maternal figure through correspondences with the writings of Jung, Foucault and Beauvoir. The objective is to discover possibilities for questioning female stigmas through artistic representation and contribute to reveal the foundations that support the patriarchal and sexist imagery. The work reflects also about the construction of evocative images in the production of a theater spectacle and the idiosyncratic processes of the viewer reception.